الإختزال في أسلوبـي التكعيبية التحليليـة والتركيبـية (دراسة مقارنـة) - فخری, م. هاوری انور (Sulaimani Journal for Humanities, 2023)
This research is concerned with the study of reduction in the two styles of analytical and synthetic cubism - a comparative study, consisting of four chapters, the first chapter of which was devoted to clarifying the research problem, its importance, its objectives, the research frames, and recognizing terminologies. The second chapter, which was prepared as a theoretical framework, contained three topics, the first of which is (The historical roots of the concept of shorthand in plastic art), through which he touches on how shorthand mechanism works, through different eras and plastic styles, and also debates about the opinions of some thinkers and philosophers regarding the relationship between art and nature of reality and the difference between the beautiful natural subject and the artistic subject (aesthetic expression), which is consistent with the title and objectives of the current research. As for the second topic, which came under the title a Brief about Analytical Cubism, it specialized in explaining the history and origins of cubism and the most prominent artists who had a role in establishing cubism. We discuss how the cubism transforms from its first phase to its second phase which is analytical cubism and how its mechanism operates. As for the third topic (a Brief about Synthetic Cubism), it considers shedding light on the third phase for cubism and it is synthetic and the prominent artists who developed this method and the new technique that they added to their work. As for the third chapter, it represented research methodology and procedures, which contained the research methodology, and through which the researcher analyzed his samples according to the descriptive analytical approach, which resulted in results that answered the research objective, and the researcher postponed its presentation with conclusions and directions to the fourth chapter, and it was found in the results that the shorthand mechanism exists in both styles, each according to the style and technique in which it was used.